KOMPETENSI PUSTAKAWAN DALAM MELAKUKAN SELEKSI KOLEKSI PERPUSTAKAAN - Yunita, Irva; Iqbal, Rahmat (Jurnal El-Pustaka, 2021)
This study aims to determine the librarians’ competencies in selecting library collection and how to improve these competencies. The method used in this research is literature study. Based on this research, it can be explained that the librarians’ competencies in selecting library collection consist of having knowledge of several things, namely their institutional programs, the collection development policies, the needs of their users, the quality of various types of collections, the credibility of publishers and providers of electronic information sources, the ability of the authors, the use of various selection tools, as well as having knowledge about information technology development plus having skills in communicating and in using various types of collection. Furthermore, to improve the competencies, librarians need to do these things: follow several trainings; read more books to increase knowledge; conduct user studies; learn how to use the selection tools; study the quality of library materials; learn everything about book publishing; seek knowledge about book editors and producers of audio-visual materials; discover what publishers who produce the best material for libraries by researching their catalogs and advertisements; and examine the national bibliography and the book trade bibliographies.